Upaya Memelihara Kebhinekaan Indonesia: Gagasan Pendidikan Multikultural di SMA BOPKRI 2 Yogyakarta - Fuji Astuti; Ardian Fahri; Mayang Indah (Universitas Negeri Gorontalo, 2026)
Education carries an important mission in shaping and developing the students’ ability to play an active role in unravelling the conflict threads of cultural community life. This article seeks to determine the development carried out by SMA BOPKRI 2 Yogyakarta in accommodating various cultures and interests in society. This article uses a qualitative research method with a phenomenological approach. The result shows that SMA BOPKRI 2 Yogyakarta which builds its branding as an Indonesia Multicultural School (SMI) appears in the learning and life processes of students in a school environment which is based on multicultural elements. Educational programs developed specifically are formulated to form new understandings and foster toleranci in students based on diversity they have. The concept of education is implemented practically and is oriented towards the diversity of Indonesia’s cultural community as a whole. Therefore, the multicultrual-based educational paradigm has the right place if it is applied to a school environment with a higher level of heterogeneity.